Analisis Perbandingan Hasil Menulis Puisi Media Konvensional dan Media Digital Pada Siswa SMP N16 Jakarat - Yahya, Zaini; Lubis, Winaria; Astuti, Tri (Jurnal Bahastra, 2024)
In this thesis the author discusses the analysis of poetry writing in conventional media and digital media in students at SMP N 16 Jakarta. Writing poetry using digital platform media will influence students' interest in creating a work. This is reflected in the large number of poems created on almost all digital media platforms. This research aims to determine the comparison between writing poetry with conventional and digital platform media based on physical and mental elements in students. And it is a consideration for students to further optimize the use of more up-to-date media to support and increase students' interest to be more enthusiastic in taking various subjects at school. The technique used in this research is a data collection technique because it uses a Quantitative Descriptive Research system. In this research, performance tests are used to assist in data management.In this thesis the author discusses the analysis of poetry writing in conventional media and digital media in students at SMP N 16 Jakarta. Writing poetry using digital platform media will influence students' interest in creating a work. This is reflected in the large number of poems created on almost all digital media platforms. This research aims to determine the comparison between writing poetry with conventional and digital platform media based on physical and mental elements in students. And it is a consideration for students to further optimize the use of more up-to-date media to support and increase students' interest to be more enthusiastic in taking various subjects at school. The technique used in this research is a data collection technique because it uses a Quantitative Descriptive Research system. In this research, performance tests are used to assist in data management.